ANALISIS KUALITAS JARINGAN INTERNET BERBASIS WIRELESS LAN MENGGUNAKAN METODE QOS (QUALITY OF SERVICE) PADA BJ’S COFFEE - Nababan, Arpan Julian Nathanael; Desiyanna Lasut (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2025)
With advances in telecommunications and information technology, we have succeeded in presenting innovative technology which is also known as internet technology. To connect millions of computers around the world to each other, a tool is needed to connect the connections between computers. Internet network protocols often face common problems such as network crashes. Network losses are caused by various factors that cause problems in network protocols, leading to network damage. Quality of Service (QoS) is the network's ability to provide services for the data traffic that passes through it, so QoS analysis is needed to solve this problem. throughput, packet loss, and delay/latency are QoS Parameters. With Wireshark, the network activity process can be easily used and can capture and analyze all types of data packets in different log formats. The design in this research has 2 parts, namely network design and system design, where the author can create a proposed design that will be made and implemented at the research agency. The prototype simulation in this research is to carry out network configuration related to the settings and management of software and hardware in a computer network. This involves performing a series of steps to set the network parameters necessary for the network to operate properly.